Dalle pietre agli alberi: celebrare Dante a Firenze fra il 1865 e il 2021 - Rossi, Federica (Opus Incertum, 2021)
For centuries, the urban fabric of Florence has been, and continues to be, shaped by a Dantean topography that includes monuments as seen by Dante, but also by works created ex novo or built according to the principles of sytlistic restoration. The article uses this framework to reflect on new and restored works that pay homage to Dante by focusing on the long-term architectural and urban-landscape transformations favoured by Dante commemorations, from the first, Risorgimento-era centennial in 1865, to that of 2021. The emblematic cases addressed regard urban decoration (Enrico Pazzi’s statue in Piazza Santa Croce), new constructions (National Central Library of Florence), and Dantean topography (Dante’s House and Dante’s Star). In every era between 1865 and 2021 works honouring Dante have served to raise awareness of topical issues. On the other hand, as Pierre Nora wrote, “Toute commémoration est une transformation de l’événement passé au service des besoins du présent”.